Islamic Education: A Contrastive Analysis of Ibn SÊnÉ’s and Al- GhazÉlÊ’s views - Hj Ariffin, Adlina (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
Ibn SÊnÉ and al-GhazÉlÊ were two great philosophers in the Muslim history. They shared in their ideas, among others, on man, society, and education. Their views on these subjects are to some extent different from each other. This paper is devoted to carry out a contrastive analysis of the ideas concerning Islamic education conceptualized by these two scholars, besides referring to their biography, their views on man, morality, society, and man’s sources of knowledge; and highlighting their contributions towards Islamic Education.